Implementasi Serqual Dalam Menentukan Tingkat Kepuasan Masyarakat Terhadap Pelayanan Pengurusan Surat Izin Usaha Mikro Dan Kecil Pada Kantor Camat Dolat Rakyat Kabupaten Karo - Junius Sembiring (Cattleya Darmaya Fortuna, 2020)
The problem faced by the community is the lack of response from the camat office employees in serving people who want to apply for business permits, this makes the quality of service at the camat office becomes inefficient. people who still do not understand in completing the required documents in processing permits, therefore the duty of the employees is to help complaints from the community so that the problems they face can be resolved quickly. Applications can be implemented using the website so that visitors are easier to provide an assessment, wherever the visitor is.